1992
DOI: 10.1121/1.403313
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic variability in the vowels of female and male speakers.

Abstract: working-class (WC) and middle-class (MC) middle-aged women. Some F m, F2 patterns are compatible with auditory predictions of a hierarchy of vocalic susceptibility to contrasting voice quality settings. [Work supported by SSHRCC.] 10:05 4SP5. Acoustic variability in the vowels of female and male speakers.When vowel formant values for female and male speakers are normalized and plotted in an F1-F2 space, it is striking that the quadrilateral spaces for the females are uniformly larger than those for the males. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0
6

Year Published

1995
1995
2007
2007

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 0 publications
4
32
0
6
Order By: Relevance
“…This raises the role of sociophonetic factors as possible key influences in determining the phonetic quality of vowel formant frequencies (e.g. Byrd, 1992Byrd, , 1994Henton, 1995;Lee et al, 1999). It is suggested that the phonetic quality of the vowel uw, may be an example of sociophonetic and/or accent variation in the 18 yearold females.…”
Section: A Formant Scaling K-age and K-sex Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…This raises the role of sociophonetic factors as possible key influences in determining the phonetic quality of vowel formant frequencies (e.g. Byrd, 1992Byrd, , 1994Henton, 1995;Lee et al, 1999). It is suggested that the phonetic quality of the vowel uw, may be an example of sociophonetic and/or accent variation in the 18 yearold females.…”
Section: A Formant Scaling K-age and K-sex Factorsmentioning
confidence: 99%
“…physiological, sociocultural, stylistic conventions) may be responsible for these and other sex-specific patterns (e.g. Byrd, 1992Byrd, , 1994Hasek et al, 1980;Henton, 1995;Lee et al, 1999;Mattingly, 1966;Traunmüller, 1984Traunmüller, , 1988.…”
Section: A Formant Scaling K-age and K-sex Factorsmentioning
confidence: 99%
See 3 more Smart Citations